2006
DOI: 10.1189/jlb.0705425
|View full text |Cite
|
Sign up to set email alerts
|

CD13 in cell adhesion: aminopeptidase N (CD13) mediates homotypic aggregation of monocytic cells

Abstract: Homotypic aggregation (HA) of cells plays key roles in physiological and pathological processes, such as embryogenesis, immune responses, angiogenesis, tumor cell invasion, and metastasis. Aminopeptidase N (CD13) has been implicated in most of these phenomena, although its participation has been attributed to its enzymatic activity, while its role as an adhesion molecule has been almost unexplored. Here, we show that certain anti-CD13 monoclonal antibodies induce HA of monocytic U-937 cells, independently of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(120 citation statements)
references
References 40 publications
8
112
0
Order By: Relevance
“…The same study also demonstrates that inhibitors of tyrosine kinases and phosphoinositide 3-kinase block the increase in calcium influx as well as the phosphorylation of MAPKs in the presence of the mAb against APN (Santos et al, 2000). In addition, antibodies to APN that have little effect on enzymatic activity exhibit a high capacity to induce cell adhesion in monocytes; this effect can be inhibited by SB203580, a p38 MAPK inhibitor (Mina-Osorio et al, 2006). APN has a very short cytoplasmic domain without any known signaling motifs (Luan and Xu, 2007) The co-distribution of SFN with APN at the leading edge of fibroblasts was unpredicted.…”
Section: Discussionmentioning
confidence: 76%
“…The same study also demonstrates that inhibitors of tyrosine kinases and phosphoinositide 3-kinase block the increase in calcium influx as well as the phosphorylation of MAPKs in the presence of the mAb against APN (Santos et al, 2000). In addition, antibodies to APN that have little effect on enzymatic activity exhibit a high capacity to induce cell adhesion in monocytes; this effect can be inhibited by SB203580, a p38 MAPK inhibitor (Mina-Osorio et al, 2006). APN has a very short cytoplasmic domain without any known signaling motifs (Luan and Xu, 2007) The co-distribution of SFN with APN at the leading edge of fibroblasts was unpredicted.…”
Section: Discussionmentioning
confidence: 76%
“…It was also reported that CD13 could block the apoptosis induction by tumor necrosis factor-alpha (26) and enhance sensitivity of tumor cells to cisplatin (27). CD13 was also proved to be involved in cell adhesion (28) as well as in endothelial invasion (29). Recent study made by Haraguchi and colleagues proved that CD13 may be a therapeutic target in human liver cancer stem cells and inhibition of CD13 by monoclonal antibody could induce cell apoptosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…CD 29 and CD 44 also are widely (Zuk et al 2002;Gimble et al 2007;Aust et al 2004;Gronthos et al 2001;De Ugarte et al 2003a, b;Katz et al 2005). CD 13, rather than being an important monocyte/ macrophage marker, plays a vital role in angiogenesis and migration (Mins-Osorio et al 2006;Pasqualini et al 2007). It is expressed in higher percentage in SF and moderately expressed in both BM and OF.…”
Section: Discussionmentioning
confidence: 99%